Challenges and backstops for development of management careers public registry (2016)
The management career is more than a technical system of personnel selection, As it generates not only the possibility of access to public employment, but that produces information relevant to the formulation of politics and decision-making in the theme of public employment through the Management Careers Public registry, however, the evolution of the administrative career, administrative and regulatory factors have prevented this registration act as a fundamental instrument for the system of management of human talent.